Analisis Pencabutan Izin Komersial Tiktok: Rekomendasi Ekonomi Digital Indonesia - Jaslin Dhabitah; Khairul Anwar Mohd Nor (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
TikTok experienced significant growth, especially during the Covid-19 pandemic. Initially, TikTok only served as an entertainment and promotional platform. In late 2021, TikTok began to diversify its services by introducing commercial functions. TikTok Shopping (Tiktokshop) provides various commercial functions, such as the ability to make transactions directly within the Tiktok app. Tiktok shop quickly gained popularity among Indonesians and created many job opportunities. However, the presence of Tiktok shop is considered to create unfair market competition. In October 2023, Tiktokshop was officially closed with the implementation of the Minister of Trade Regulation No. 31 of 2023. The main objective of this research is to investigate the revocation of Tiktok shop licenses and provide recommendations for digital economy regulation in Indonesia. This article uses a qualitative methodology with a case study technique. The research findings show that prohibiting social commerce platforms from allowing direct payments could limit innovation in Indonesia's digital economy. The rapid advancement of technology makes current regulations insufficient to accommodate change and innovation. Therefore, authorities can use a regulatory sandbox approach in regulating the digital economy. This can facilitate innovation while protecting the interests of the wider public so that Indonesia's digital economy is not left behind.